Caracasine acid, an ent-3,4-seco-kaurene, promotes apoptosis and cell differentiation through NFkB signal pathway inhibition in leukemia cells - Martinez, Gricelis Patricia; Mijares, Michael Rodney; Chávez, Katiuska; Suarez, Alirica Isabel; Compagnone, Reinaldo Santi; Chirinos, Perla; De Sanctis, Juan Bautista (European journal of pharmacology, 2019)
Caracasine acid (CA) is an ent-3,4-seco-kaurene isolated from the plant Croton micans. Decreased cancer cell lines viability was reported upon CA treatment. The present study aimed to investigate the mechanism of CA induced cytotoxicity using two human cell lines, Jurkat E6.1 (human cell T lymphoma) and HL-60 (human acute promyelocytic leukemia). Significant increases of apoptotic cell death markers upon CA treatment were observed: annexin-V positiveness, potential mitochondrial disturbances, cell cycle changes, caspase activation, and CD95 expression. These effects were not detected in normal lymphocytes. CA induced the appearance of Bax, cleaved caspase 3, and cytochrome c release in Jurkat cells, and cleaved caspase 3 and phosphorylated p53 in HL60 cells. Likewise, downregulation of anti-apoptotic proteins such as Bcl-x (Jurkat), Bcl-2, and XIAP (HL60) was observed with CA treatment. Both pathways, intrinsic and extrinsic were activated when cell lines were treated with CA. NF-κB p65 inhibition was observed in Jurkat cells and cell differentiation in HL-60 cells. CA could be a potential leader compound for the development of new drugs for leukemia treatment in humans.
Keywords: Cancer; Kaurene compounds; signální transdukce; leukemie; apoptóza; lidé; Signal Transduction; diterpeny kauranové; Humans; Antineoplastic Agents, Phytogenic; Leukemia; Diterpenes, Kaurane; viabilita buněk; HL-60 Cells; Annexin-V; Caracasine acid; screeningové testy protinádorových léčiv; Cell Differentiation; Transcription Factor RelA; Apoptosis; Jurkat buňky; Drug Screening Assays, Antitumor; Jurkat Cells; fytogenní protinádorové látky; transkripční faktor RelA; HL-60 buňky; Croton; buněčná diferenciace; Cell Survival; NF-κB